AMPK/PPAR-γ/NF-κB axis participates in ROS-mediated apoptosis and autophagy caused by cadmium in pig liver. (1st February 2022) - Wang, Huan; Wang, Anqi; Wang, Xinqiao; Zeng, Xiangyin; Xing, Houjuan
Abstract: The experiment was conducted to investigate the effects of Cadmium (Cd) on growth performance, blood biochemical parameters, oxidative stress, hepatocyte apoptosis and autophagy of weaned piglets. A total of 12 healthy weaned piglets were randomly assigned to the control and the Cd group, which were fed with a basal diet and the basal diet supplemented with 15 ± 0.242 mg/kg CdCl2 for 30 d, respectively. Our results demonstrated that Cd significantly decreased final body weight, average daily feed intake (ADFI), average daily gain (ADG) and increased feed-to-gain (F/G) ratio ( P < 0.05). For blood biochemical parameters, Cd treatment significantly decreased the red blood cell (RBC), hemoglobin (HGB), hematocrit (HCT), total protein, albumin, copper content and iron content ( P < 0.05). In addition, liver injury was observed in the Cd-exposed group. Our results also demonstrated that Cd exposure contributed to the production of ROS, activated the AMPK/PPAR-γ/NF-κB pathway (increasing the expressions of P-AMPK/AMPK, NF-κB, I-κB-β, COX-2, and iNOS, decreasing the expressions of PPAR-γ and I-κB-α), finally induced autophagy (increasing the expressions of Beclin-1, the ratio of LC3-II/LC3-I and p62), and apoptosis (increasing the expressions of Bax, Bak, Caspase-9, and Caspase-3, decreasing the expression of Bcl-2). Overall, these findings revealed the vital role of AMPK/PPAR-γ/NF-κB pathway in Cd-induced liver apoptosis and autophagy, which provided deeper insights into a better understanding of Cd-induced hepatotoxicity. Graphical abstract: Image 1 Highlights: Cd exposure caused hepatotoxicity. Apoptosis and autophagy occurred in weaned pig liver induced by Cd. AMPK/PPARγ/NF-κB axis participated in Cd-induced liver injury of pigs. The damage to the degradation process led to defects in autophagy.